2010
DOI: 10.1016/j.envint.2009.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of mechanism(s) of DNA damage induced by 4-monochlorobiphenyl (PCB3) metabolites

Abstract: Abstract4-Monochlorobiphenyl (PCB3) is readily converted by xenobiotic-metabolizing enzymes to dihydroxy-metabolites and quinones. The PCB3 hydroquinone (PCB3-HQ; 2-(4'-chlorophenyl)-1,4-hydroquinone) induces chromosome loss in Chinese Hamster V79 cells, whereas the para-quinone (PCB3-pQ; 2-(4'-chlorophenyl)-1,4-benzoquinone) very efficiently induces gene mutations and chromosome breaks. Apparently, each of these two metabolites, which are a redox pair, has a different spectrum of genotoxic effects due to diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 73 publications
(94 reference statements)
0
25
0
Order By: Relevance
“…DDR signaling involves a large number of proteins that act as sensors, mediators, transducers and effector proteins [41,42]. Recruitment of the DDR protein γ-H2AX, BRCA1, and 53BP1 to DNA DSBs is a key event in the DDR [43-45]. Defective recruitment of repair factors at DNA DSBs, such as delay in foci assembly and disassembly, is associated with defective DDR.…”
Section: Discussionmentioning
confidence: 99%
“…DDR signaling involves a large number of proteins that act as sensors, mediators, transducers and effector proteins [41,42]. Recruitment of the DDR protein γ-H2AX, BRCA1, and 53BP1 to DNA DSBs is a key event in the DDR [43-45]. Defective recruitment of repair factors at DNA DSBs, such as delay in foci assembly and disassembly, is associated with defective DDR.…”
Section: Discussionmentioning
confidence: 99%
“…Although for a long time PCBs were thought to be strictly promoting carcinogens, a lower chlorinated congener (PCB3) was shown to induced point mutations in rat livers in vivo (Lehmann et al, 2007), and, in agreement with this, recent evidence suggests that particularly the lower-chlorinated congeners can be oxidized to genotoxic metabolites, such as arene oxides and quinone species (Espandiari et al, 2003, Espandiari et al, 2004, Robertson and Ludewig, 2011). In fact, the quinone metabolites of PCB3 increase gene mutations in vitro at low micromolar concentrations (Zettner et al, 2007), induce strand breaks (Xie et al, 2010), bind to and inhibit the nuclear protein topoisomerase II (Bender et al, 2006, Bender and Osheroff, 2007, Srinivasan et al, 2001, Srinivasan et al, 2002) and reduce telomerase activity resulting in shortened chromosomal telomeres in cells in culture (Jacobus et al, 2008). Interestingly, only the para -dihydroxy metabolite of PCB3 induced polyploidization and only the ortho -dihydroxy metabolite caused sister chromatid exchanges (Flor and Ludewig, 2010) indicating a binding to other, so far unidentified cellular proteins, as mediators of these genotoxic effects.…”
Section: Pcb Metabolite Associated Toxicitiesmentioning
confidence: 99%
“…As described above, the chlorination pattern of a PCB congener determines the substrate specificity for CYP forms which in turn my influence organ and cell-specific formation of oxidized metabolites. In addition, cells with specific oxidizing enzymes, like myeloperoxidase in bone marrow cells, may be most likely to produce reactive quinone metabolites and therefore more likely to form DNA and protein adduct (Xie et al, 2010). Understanding of these specific enzyme requirements may elucidate the mechanism of the observed organ-specific carcinogenicity of 34 PCBs.…”
Section: Toxicological Relevance Of Pcb Metabolites and Research Needsmentioning
confidence: 99%
“…PCB3-HQ is oxidized by MPO in HL-60 cells with the generation of ROS and induction of DNA damage. However, this is not the case with the PCB3-pQ, which may produce DNA damage by the reactivity of the quinone with the DNA or nuclear proteins, or possibly by indirectly increasing intracellular ROS levels by glutathione (GSH) depletion [10]. All the phenolic compounds were able to oxidize DNA bases in human lymphocytes, and also observed that pyrimidine bases were more strongly oxidized in comparison to purine ones.…”
Section: Recent In Vitro Assays For Oxidative Dna Damages With Industmentioning
confidence: 90%